The Role of Managements in Improving Local Government Performance in Indonesia: Proceed. 2nd UMY-IIUM International Joint Seminar - Suryo Pratolo, Rizal Yaya., dkk (UMY & IIUM, 2009)
The Role of Managements in Improving Local Government Performance in Indonesia